PENGARUH SISTEM AKUNTANSI KEUANGAN, TEKNOLOGI INFORMASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI LINGKUNGAN PEMERINTAH KABUPATEN TEBO - Eva Setiarini Damanik (Universitas Batanghari Jambi, 2017)
The purpose of this study is to examine the influence of financial accounting system, information technology and organizational commitment on the performance of SKPD. The independent variables of this study were financial accounting system, information technology and organizational commitment, moreover, the dependent variable was the performance of SKPD. This study was conducted by taking a sample of head on regional working units, financial administration officials, and the financial staff at the local government unit in the Tebo district administration office. The hypothesis empirically tested using multiple linear regression analysis. Statistical test results showed that the financial accounting system, information technology and organizational commitment simultaneously affect the performance of SKPD. Financial accounting system and organizational commitment partially positive and significant impact on the performance of SKPD, moreover information technology does not significantly influence of the performance of SKPD.Keywords: financial accounting system, information technology, organizational commitment, performance of SKPD.